Research on Mining-Induced Stress Distribution of Extrathick Coal Seams Based on Electromagnetic Wave CT Technology - Tuan He; Guodong Li; Feng Luo; Xueqing Li (Advances in Civil Engineering)
Fully mechanized caving mining in extrathick coal seams is currently the most efficient mining method. To figure out the mining-induced stress in extrathick coal seams which is significantly different from the normal ones is essential for mining safety. This research is based on the No. 3106 working face of Lu-Zi-Gou coal mine in China, which extracts extrathick coal seams by using the comprehensive mechanized top-coal caving method. According to the elastoplastic theory, a multiforce superposition mining-induced stress model is constructed in this research. In this model, the mining-induced stress is generated by the side coal seam of the stope, including the load formed by the broken roof blocks in the caving zone, the unbroken rock layers in the side of the goaf, and the rock layers in the bending zone. To verify the model, electromagnetic wave CT detection and borehole endoscopy are used to test the coal’s electromagnetic wave attenuation and internal joints. The results indicate that the mining of extrathick coal seams forms internal and external stress fields in the side coal seams of the stope. As the depth increases, the mining-induced stress first increases and then decreases within the two areas. According to the above conclusions, the width of coal pillars and the location of roadways between adjacent working faces can be reasonably determined.